2017
DOI: 10.1093/pcp/pcx187
|View full text |Cite|
|
Sign up to set email alerts
|

Type-B ARRs Control Carpel Regeneration Through Mediating AGAMOUS Expression in Arabidopsis

Abstract: Plants are known for their capacity to regenerate organs, such as shoot, root and floral organs. Recently, a number of studies contributed to understanding the mechanisms of shoot and root regeneration. However, the mechanisms underlying floral organ regeneration are largely unknown. In this study, we established a carpel regeneration system in which two types of carpels were induced by exogenous cytokinin. For type I, all the floral organs in the regenerated inflorescence were transformed into carpels. For ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…In Arabidopsis, disruption of this pathway at multiple stages has resulted in modified reproductive development, with cytokinin typically being implicated in enhancing development of female floral parts [46]. For example, it has recently been shown that the Type B response regulators ARR1 and ARR10 bind to the promoter region of the floral homeotic gene AGAMOUS , and down-regulation of these genes inhibits carpel regeneration in an in vitro assay [49]. Similarly, triple mutants of ARR1 , ARR10 , and ARR12 have severely compromised gynoecial development [50].…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, disruption of this pathway at multiple stages has resulted in modified reproductive development, with cytokinin typically being implicated in enhancing development of female floral parts [46]. For example, it has recently been shown that the Type B response regulators ARR1 and ARR10 bind to the promoter region of the floral homeotic gene AGAMOUS , and down-regulation of these genes inhibits carpel regeneration in an in vitro assay [49]. Similarly, triple mutants of ARR1 , ARR10 , and ARR12 have severely compromised gynoecial development [50].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, carpel regeneration was impaired in AG amiRNA lines, confirming the requirement of this gene during carpel formation. Although these experiments were performed in a carpel-inducing system, they suggest that the cytokinin-dependent control of AG expression, through ARR1 and ARR10, might also be functional during normal carpel development [27].…”
Section: Flower Developmentmentioning
confidence: 99%
“…For example, in loss-of-function lines of ARR1 and ARR10, carpel (see Glossary) regeneration from callus was impaired [27]. These B-type ARRs were shown to bind the AGAMOUS (AG) promoter region and induce expression of this carpel identity defining gene.…”
Section: Flower Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the flower number can be controlled by modulating the cytokinin levels.At the early flower developmental stage of a meristem-organizing center to be formed, cytokinins establish the meristematic competence of the floral meristem [23]. During pistil establishment, the cytokinin signaling B-type regulators ARABIDOPSIS RESPONSE REGULATOR (ARR)1 and ARR10 bind to the promoter of AGAMOUS (AG) and thereby induce expression of this carpel identity gene [24]. In addition, the pistils were absent in rice log mutant, in which active cytokinin levels were reduced [11], and absence of the SHOOT MERISTEMLESS (STM) gene, an activator of cytokinin biosynthesis, in Arabidopsis also results in the production of flowers without pistils.…”
mentioning
confidence: 99%